2019
DOI: 10.1016/j.ajogmf.2019.100041
|View full text |Cite
|
Sign up to set email alerts
|

Maternal body mass index and pregnancy outcomes: a systematic review and metaanalysis

Abstract: T he global prevalence of obesity (body mass index [BMI], 30 kg/m 2 ) has tripled since 1975, and it is estimated that, in 2016, >1.9 billion adults were overweight (BMI, 25e29.9 kg/m 2 ), of which >650 million adults were obese. 1 Among women giving birth in the United States in 2014, 50.4% were either overweight or obese. 2 In addition, adults with a BMI of kg/m 2 comprise the most rapidly growing class of obesity in the United States. 3 Pregnant women who are classified as overweight or obese are known to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
84
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(93 citation statements)
references
References 28 publications
5
84
1
3
Order By: Relevance
“…The protocol has been registered with PROSPERO (CRD42017074290). This protocol covered two distinct systematic reviews – the first looking at the incidence of complications stratified by increasing BMI, the findings of which have been published separately, 2 and the second, which is the focus of this manuscript. This review was conducted and reported according to the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) and meta‐analysis of observational studies in epidemiology (MOOSE) guidelines respectively 8,9 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The protocol has been registered with PROSPERO (CRD42017074290). This protocol covered two distinct systematic reviews – the first looking at the incidence of complications stratified by increasing BMI, the findings of which have been published separately, 2 and the second, which is the focus of this manuscript. This review was conducted and reported according to the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) and meta‐analysis of observational studies in epidemiology (MOOSE) guidelines respectively 8,9 …”
Section: Methodsmentioning
confidence: 99%
“…While women with BMI 30‐39.9 kg/m 2 seldom pose a clinical dilemma with regard to determining the mode of birth, those with a BMI ≥ 40 kg/m 2 are at increased risk for complications during childbirth. A recent systematic review comparing pre‐existing medical conditions and pregnancy outcomes stratified by BMI, showed that when compared with pregnant women with BMI 18.5‐24.9 kg/m 2 (n = 1 905 339), those with BMI ≥ 40 kg/m 2 (n = 82 691) are at increased risk for entering pregnancy with pre‐existing diabetes (4.14% vs 0.71%, relative risk (RR) 6.58) and essential hypertension (8.86% vs 0.69%, RR 12.37), and also of developing gestational diabetes (17.01% vs 3.85%, RR 4.62) and hypertensive disorders during pregnancy (15.86% vs 3.46%, RR 4.55) 2 . These conditions, as well as other factors such as a poor response to labor induction 3 and augmentation, 3 protracted labor courses, 4 and fetal macrosomia (12.86% vs 6.18%, RR 2.55), 2 result in a higher rate of planned‐ (29.81% vs 17.33%, RR 1.67) and unplanned (21.72% vs 13.92%, RR 1.53) cesarean delivery (CD), 2 and an associated increase in wound complications 5 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well established that women with obesity are at increased risk for adverse pregnancy outcomes and that their children are at risk for childhood obesity, as well as metabolic disease in later life . Published and ongoing clinical trials explore interventions to improve outcomes for these women and children.…”
Section: Introductionmentioning
confidence: 99%